The importance of involving high-school chemistry teachers in the process of defining the operational meaning of 'chemical literacy' - Shwartz, Yael; Ben-Zvi, Ruth; Hofstein, Avi (International journal of science education, 2005)
The ongoing reform in science education in many countries, including Israel, has attainment of scientific literacy for all as one of its main goals. In this context, it is important to provide teachers with the opportunity to construct meaning for the term science literacy and by doing so to obtain a clear understanding of the new teaching goals. Here we report on a study in which teachers, as part of their professional development, were involved in defining the term 'chemical literacy'; they discussed the need for it, and suggested educational experiences that are necessary in order to attain it. The programme was conducted as part of a reform in the content, as well as in the pedagogy, of chemistry education in Israel. The collected data provide some insights regarding the process by which the teachers' perception of 'chemical literacy' developed and the way actual school practice influences teachers' perception of 'chemical literacy'.